Pulmonary Arterial Hypertension: A Deeper Evaluation of Genetic Risk in the -Omics Era - Rajiv D. Machado (MDPI AG, 2021)
Pulmonary arterial hypertension (PAH) is a highly heterogeneous disorder with a complex, multifactorial aetiology [...]